Isothermal grain coarsening of spray formed alloys in the semi-solid state - Manson-Whitton, E; Stone, I; Jones, JR; Grant, P; Cantor, B (2002)
Grain coarsening of alloys in the semi-solid state is important in controlling grain sizes in spray forming and in other processes in which an alloy is formed or cast in the semi-solid state. Until now, this coarsening has been analysed in terms of classic LSW theory or in terms of the migration of grain boundary liquid films. These analyses suggest that the coarsening rate should increase with increasing solid fraction, f S, but this suggestion conflicts with previous experimental results which show that coarsening rate decreases with increasing f S for f S > 0.7. This paper shows, for the first time, that coarsening rate does increase with f S for f S less than approximately 0.75 in agreement with the liquid film migration model, and then decreases again with further increasing f S for f S greater than approximately 0.75. A modified model of liquid film migration is proposed which takes into account the reducing area of the liquid film as f S increases for high f S. The formation of intragranular liquid droplets, and the pinning of grain boundary liquid films by dispersoids during coarsening are also discussed. © 2002 Acta Materialia Inc. Published by Elsevier Science Ltd. All rights reserved.